Open‐label study to evaluate trifluridine/tipiracil safety, tolerability and pharmacokinetics in patients with advanced solid tumours and hepatic impairment. Issue 6 (28th March 2019) - Saif, Muhammad Wasif; Rosen, Lee; Rudek, Michelle A.; Sun, Weijing; Shepard, Dale R.; Becerra, Carlos; Yamashita, Fumiaki; Bebeau, Paul; Winkler, Robert
Abstract : Aims: Trifluridine/tipiracil (FTD/TPI) prolongs survival in refractory metastatic colorectal cancer, but limited data exist on its use in patients with hepatic impairment. This Phase I, open‐label, nonrandomized study investigated the safety, tolerability and pharmacokinetics of FTD/TPI in patients with advanced solid tumours (except breast cancer) and varying degrees of hepatic impairment, to provide dosing recommendations. Methods: Patients aged ≥18 years with advanced solid tumours and normal hepatic function, or mild, moderate or severe hepatic impairment according to National Cancer Institute criteria, were planned to be enrolled. Patients received FTD/TPI 35 mg/m 2 orally twice daily on days 1–5 and 8–12 of each 28‐day cycle. Results: Twenty‐four patients were enrolled to the normal hepatic function ( n  = 8) and mild ( n  = 10) and moderate ( n  = 6) hepatic impairment cohorts. Overall, 12 patients (50.0%) had at least 1 adverse event leading to study discontinuation. In the moderate hepatic impairment cohort, 5 of 6 patients experienced grade ≥ 3 elevation in bilirubin. No patients with severe hepatic impairment were enrolled. FTD area under the curve at steady state decreased by 18% and 22% in the mild and moderate cohorts, respectively; however, no clear change was observed in TPI area under the curve. Conclusions: FTD/TPI can be safely administered in patients with normal hepatic function and mild hepatic impairment, with no initial dose adjustment. FTD/TPI is not recommended for use in patients with moderate hepatic impairment because of findings of grade 3 or 4 increased blood bilirubin. Therefore, FTD/TPI is not recommended for patients with moderate or severe hepatic impairment.